2009
DOI: 10.1007/s00122-009-0962-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and chromosomal location of Pm40 in common wheat: a new gene for resistance to powdery mildew derived from Elytrigia intermedium

Abstract: Powdery mildew, caused by Blumeria graminis f. sp. tritici, is a very destructive wheat (Triticum aestivum) disease. Resistance was transferred from Elytrigia intermedium to common wheat by crossing and backcrossing, and line GRY19, that was subsequently selected, possessed a single dominant gene for seedling resistance. Five polymorphic microsatellite markers, Xgwm297, Xwmc335, Xwmc364, Xwmc426 and Xwmc476, on chromosome arm 7BS, were mapped relative to the powdery mildew resistance locus in an F(2) populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
82
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(86 citation statements)
references
References 22 publications
0
82
0
3
Order By: Relevance
“…is a hexaploid species (2n=6x=42) with genomes E 1 E 2 St (Wang et al 1994) or JJ S St (Chen et al 1998). The species has been hybridized extensively with wheat and proved to be a valuable source of genes for disease resistance (Larkin et al 1995;Chen et al 2003;Yang et al 2006;Luo et al 2009) and tolerance to salt stress (Dvořák 1985). The correct identification of Th.…”
mentioning
confidence: 99%
“…is a hexaploid species (2n=6x=42) with genomes E 1 E 2 St (Wang et al 1994) or JJ S St (Chen et al 1998). The species has been hybridized extensively with wheat and proved to be a valuable source of genes for disease resistance (Larkin et al 1995;Chen et al 2003;Yang et al 2006;Luo et al 2009) and tolerance to salt stress (Dvořák 1985). The correct identification of Th.…”
mentioning
confidence: 99%
“…The results showed that SN100109 was immune to E01, E18, E23-2, E30-1, and E32; and highly resistant to E09, E17, E21, E23-1, E26, E31, E49, and E50; and resistant to E02, E13, and E16. Compared with Pm40 (Luo et al 2009) and Pm43 (He et al 2009), which also derived from Th. intermedium, SN100109 and GRY19 (Pm40) had different resistance reactions to Bgt races E05, E06, E07, E16, and E21.…”
Section: Characteristics Of Sn100109 Resistance To Powdery Mildewmentioning
confidence: 95%
“…The results infer that the resistance gene in SN100109 lies on the additional 2J chromosomes. Gene Pm40 (Luo et al 2009) and Pm43 (He et al 2009) also derived from Th. intermedium.…”
Section: Resistance To Powdery Mildew In Sn100109mentioning
confidence: 99%
See 1 more Smart Citation
“…The shift in pathogenic virulence structures range from the southwest and the southeast coastal regions of China to almost all the wheat growing areas throughout the country and the damage exceeds any other known wheat disease (Liu and Shao, 1994;Luo et al, 2009;Cao et al, 2013;Zhao et al, 2013;Shen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%